2022
DOI: 10.1186/s12913-022-07525-1
|View full text |Cite
|
Sign up to set email alerts
|

The attitude and acceptability towards medical promotional tools and their influence on physicians’ prescribing practices in Jordan and Iraq: a cross-sectional study

Abstract: Background Pharmaceutical companies spend more than one-third of their sales revenue on marketing and promotion directed toward healthcare professionals. There has been a focus on the relationship between healthcare professionals and the pharmaceutical industry in recent years. This study aims to explore the attitude toward and acceptability of medical promotional tools and their influence on physicians’ prescribing practices in Jordan and Iraq. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The relationship among health care providers, patients, and industrial device representatives is a conditio sine qua non in the field of neuromodulation. Despite the disputable role of industry-sponsored randomized controlled trials of drugs and medical devices toward more favorable results compared with non–industry-sponsored trials [ 46 ] and the influence of medical promotional tools provided by medical representatives on physicians’ prescribing practices [ 47 ], in total, 43.5% of the retrieved information referred to a specific industrial partner (directly or indirectly). Notwithstanding the considerable involvement of device manufacturers, web-based information is not limited to commercial information about the different types of materials and IPGs, as revealed by the heterogeneity of detected themes and subthemes in the content analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship among health care providers, patients, and industrial device representatives is a conditio sine qua non in the field of neuromodulation. Despite the disputable role of industry-sponsored randomized controlled trials of drugs and medical devices toward more favorable results compared with non–industry-sponsored trials [ 46 ] and the influence of medical promotional tools provided by medical representatives on physicians’ prescribing practices [ 47 ], in total, 43.5% of the retrieved information referred to a specific industrial partner (directly or indirectly). Notwithstanding the considerable involvement of device manufacturers, web-based information is not limited to commercial information about the different types of materials and IPGs, as revealed by the heterogeneity of detected themes and subthemes in the content analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Data analysis was an ongoing process which started during data collection and proceeded iteratively. The interviews were transcribed by NHH or WNAWI, checked by HS and read repeatedly to gain an overall sponsor's medication which could lead to irrational prescribing [9][10][11][12][13]. A study reported that 75% of their studied population felt that information given by pharmaceutical representatives is 'not trustworthy' while 47.6% felt that the information provided to them helps them to learn about new drugs and to keep them updated [14].…”
Section: Discussionmentioning
confidence: 99%
“…from Iraq and Jordon has even reported that some MRs have a negative attitude toward their competitors’ products. [ 32 ]…”
Section: Discussionmentioning
confidence: 99%